Potent Lymphatic Translocation and Spatial Control Over Innate Immune Activation by Polymer–Lipid Amphiphile Conjugates of Small‐Molecule TLR7/8 Agonists. Issue 43 (12th September 2019) - De Vrieze, Jana; Louage, Benoit; Deswarte, Kim; Zhong, Zifu; De Coen, Ruben; Van Herck, Simon; Nuhn, Lutz; Kaas Frich, Camilla; Zelikin, Alexander N.; Lienenklaus, Stefan; Sanders, Niek N.; Lambrecht, Bart N.; et al.
Abstract: Uncontrolled systemic inflammatory immune triggering has hampered the clinical translation of several classes of small‐molecule immunomodulators, such as imidazoquinoline TLR7/8 agonists for vaccine design and cancer immunotherapy. By taking advantage of the inherent serum‐protein‐binding property of lipid motifs and their tendency to accumulate in lymphoid tissue, we designed amphiphilic lipid–polymer conjugates that suppress systemic inflammation but provoke potent lymph‐node immune activation. This work provides a rational basis for the design of lipid–polymer amphiphiles for optimized lymphoid targeting. Abstract : Two‐faced : Lipid–polymer amphiphile conjugates of potent small‐molecule immunomodulators (TLR7/8a) bind to serum proteins like albumin, thereby restricting innate immune activation to lymphoid tissue. This work provides a rational basis for the design of lipid–polymer amphiphiles for optimized lymphoid targeting.